Socioeconomic determinants for compliance to colorectal cancer screening. A multilevel analysis. Issue 4 (8th September 2009) - Pornet, C; Dejardin, O; Morlais, F; Bouvier, V; Launoy, G
Abstract : Background: Compliance in cancer screening among socially disadvantaged persons is known to be lower than among more socially advantaged persons. However, most of the studies regarding compliance proceed via a questionnaire and are thus limited by self-reported measures of participation and by participation bias. This study aimed at investigating the influence of socioeconomic characteristics on compliance to an organised colorectal cancer screening programme on an unbiased sample based on data from the entire target population within a French geographical department, Calvados (n=180 045). Methods: Individual data of participation and aggregate socioeconomic data, from the structure responsible for organising screening and the French census, respectively, were analysed simultaneously by a multilevel model. Results: Uptake was significantly higher in women than in men (OR=1.33; 95% CI 1.21 to 1.45), and significantly lower in the youngest (50–59 years) and in the oldest (70–74 years) persons, compared with intermediate ages (60–69 years), with OR=0.70 (95% CI 0.63 to 0.77) and OR=0.82 (95% CI 0.72 to 0.93), respectively. Uptake fell with increasing level of deprivation. There was a significant difference of uptake probability between the least deprived and the most deprived areas (OR=0.68; 95% CI 0.59 to 0.79). No significant influence of the general practitioners density was found. Conclusion: Multilevel analysis allowed to detect areas of weak uptake linked to areas of strong deprivation. These results suggest that targeting populations with a risk of low compliance, as identified both socially and geographically in our study, could be adopted to minimise inequalities in screening.